Language Learning and Learner Psychology: Building Autonomy in Multilingual Culture - Ramadhan Mahendra; Sulis Triyono (RETORIKA: Jurnal Ilmu Bahasa, 2019)
The notion of autonomous learning used in second language learning has become a focal point of scholars in recent years. However, building an autonomy in specific language learners might be different in the view of psychology within multilingual culture which raised interesting issues. However, learners’ psychology determines about how far they must learn the second language. In addition, the multilingual culture has important role as variable but in an abstract way. It appears that in some languages learners who had multilingual culture backgrounds have different situation in comprehending the English, which also affect in choosing suitable learning strategies to comprehend by their own. Therefore, this research addresses to find out the interrelation in case of building leaner autonomy on English as second language learning in the aspect of multilingual culture in Indonesia. Trough library research, the author found the correlation between learners’ psychological condition such as interest, needs and motivation has some impact on how successful in their own language learning within the multilingual culture as it background. Therefore, building autonomy in second language learning must be aware of multilingual and social culture in society to reap a good result.